(untitled) (Journal of Life and Earth Science, 2014)
Small Indigenous Species (SIS) of fishes of 18 species under ten families and five orders were selected for the experiment. The percentage and ratio of edible portions compared to their wastes (%) were determined. The percentage by weight after dressing and washing was found for Corica soborna as 97.76% and the lowest for Colisa fasciata as 57.40%, but the ratio of these weights were maximum on C. fasciata and minimum in C. soborna. DOI: http://dx.doi.org/10.3329/jles.v7i0.20129 J. Life Earth Sci., Vol. 7: 105-108, 2012